Does Quantum Chaos Exist? - Knauf, Andreas (Chance in Physics, 2001)
The usual operational definition of the term ‘Quantum Chaos’, meaning a quantum system whose classical counterpart is non-integrable, is not self-contained. However it is argued that there cannot be any intrinsic definition of chaoticity of a finite quantum system which is not based on some kind of semiclassical limit. Unlike for finite systems, the quantum dynamical entropy of infinite systems may be strictly positive. However, an example shows that this quantity may be lowered by interactions which lead to an increase of classical dynamical entropy.
UnivIS-Import:2015-04-20:Pub.2001.nat.dma.lma6.doesqu